2021
DOI: 10.1007/s11126-021-09943-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of SARS-CoV-2 (COVID-19) and its Lockdown Measures on the Mental and Functional Health of Older Individuals

Abstract: The effect of the COVID-19 on the physical and mental health of Italian older individuals displaying signs of cognitive deterioration has not been deeply investigated. This longitudinal study examined the impact of COVID-19 lockdown measures on the psychological well-being and motor efficiency of a sample of Italian community-dwellers with and without cognitive decline. Forty-seven participants underwent instrumental gait analysis performed in ecological setting using wearable sensors, and completed a battery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(41 reference statements)
0
1
0
Order By: Relevance
“… 32 Similarly, living together with a partner in the same household seemed to serve as a protective buffer against worsening SRH, because social ties have an impact on mental and physical health. 33 This is particularly true for living together with partners 34 and partly explains why in our study respondents who were not living with their partner in the same household were more likely to show worsened SRH. Findings from other studies are in line with this interpretation and reported that social support and family functioning were consistently positively associated with health and well-being.…”
Section: Discussionmentioning
confidence: 60%
“… 32 Similarly, living together with a partner in the same household seemed to serve as a protective buffer against worsening SRH, because social ties have an impact on mental and physical health. 33 This is particularly true for living together with partners 34 and partly explains why in our study respondents who were not living with their partner in the same household were more likely to show worsened SRH. Findings from other studies are in line with this interpretation and reported that social support and family functioning were consistently positively associated with health and well-being.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, about 50 % of the entrepreneurs in the study, about 57%, expressed concern about their and their family's health, and 39.7% of the participants said they had faced great uncertainty and unpredictable events at work. Scientific research on the effects of the pandemic on mental health has focused on the general population and specific subgroups, such as women (Bittmann, 2021;Huebener et al, 2021;Nwafor et al, 2020;Suso-Ribera & Martín-Brufau, 2020), the elderly (Fastame et al, 2021), healthcare professionals (Foye et al, 2021;Greenberg et al, 2020;Ornell et al, 2021;Reiser et al, 2021), and academics (Chaturvedi et al, 2021;Chirikov, 2020;Mansur-Alves et al, 2021). However, an important subgroup of the population has been neglected in studies on the effects of the Covid-19 pandemic on mental health.…”
Section: Alvesmentioning
confidence: 99%